LOCAL COMMUNITY PARTICIPATION ON INTELLECTUAL PROPERTY RIGHTS PROTECTION OF CIREBON BATIK - Josefhin Mareta (Jurnal Dinamika Hukum, 2017)
Legal protection of batik art owned by local communities cannot be totally implemented in the legal system of intellectual property rights. The implementation of legal awareness by batik artisans in protecting the traditional knowledge and use of legal effort for the protection of intellectual property is still low. This study was conducted to analyze the participation of local people in the protection of intellectual property rights of Cirebon batik. This study employed qualitative research methods. Based on the results of the study, it is concluded that Cirebon local government have provided legal counseling on the protection of intellectual property rights yet the participation of batik artisans is still low due to the assumption of batik as communal property. Hence, local regulations are necessarily needed to assure intellectual property rights of Cirebon batik.Keywords: Community Participation, Intellectual Property Rights, Cirebon Batik